Eigenvalue measurement of topologically protected edge states in split-step quantum walks - Nitsche, Thomas; Geib, Tobias; Stahl, Christoph; Lorz, Lennart; Cedzich, Christopher; Barkhofen, Sonja; Werner, Reinhard F; Silberhorn, Christine (New Journal of Physics)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Controllable high-speed polariton waves in a PT-symmetric lattice - Ma, Xuekai; Kartashov, Yaroslav Y; Gao, Tingge; Schumacher, Stefan (New Journal of Physics)

High-speed velocimetry in microfluidic protein mixers using confocal fluorescence decay microscopy - Inguva, Venkatesh; Rothstein, Jonathan P.; Bilsel, Osman; Perot, Blair J. (Experiments in Fluids)

Quantum state and mode profile tomography by the overlap - Tiedau, J; Shchesnovich, V S; Mogilevtsev, D; Ansari, V; Harder, G; Bartley, Tim; Korolkova, N; Silberhorn, Christine (New Journal of Physics)

Systematic study of the influence of coherent phonon wave packets on the lasing properties of a quantum dot ensemble - Wigger, Daniel; Czerniuk, Thomas; Reiter, Doris E; Bayer, Manfred; Kuhn, Tilmann (New Journal of Physics)
Coherent phonons can greatly vary light–matter interaction in semiconductor nanostructures placed inside an optical resonator on a picosecond time scale. For an ensemble of quantum dots (QDs) as active laser medium, phonons are able to induce a large enhancement or attenuation of the emission intensity, as has been recently demonstrated. The physics of this coupled phonon–exciton–light system consists of various effects, which in the experiment typically cannot be clearly separated, in particular, due to the complicated sample structure a rather complex strain pulse impinges on the QD ensemble. Here we present a comprehensive theoretical study how the laser emission is affected by phonon pulses of various shapes as well as by ensembles with different spectral distributions of the QDs. This gives insight into the fundamental interaction dynamics of the coupled phonon–exciton–light system, while it allows us to clearly discriminate between two prominent effects: the adiabatic shifting of the ensemble and the shaking effect. This paves the way to a tailored laser emission controlled by phonons.

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Driven discrete time quantum walks - Hamilton, Craig S; Barkhofen, Sonja; Sansoni, Linda; Jex, Igor; Silberhorn, Christine (New Journal of Physics)

Quantum walks with dynamical control: graph engineering, initial state preparation and state transfer - Nitsche, Thomas; Elster, Fabian; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Barkhofen, Sonja; Silberhorn, Christine (New Journal of Physics)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Direct generation of genuine single-longitudinal-mode narrowband photon pairs - Luo, Kai-Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine (New Journal of Physics)

A population-competition model for analyzing transverse optical patterns including optical control and structural anisotropy - Tse, Y C; Chan, Chris K P; Luk, M H; Kwong, N H; Leung, P T; Binder, R; Schumacher, Stefan (New Journal of Physics)

Directly comparing entanglement-enhancing non-Gaussian operations - Bartley, Tim; Walmsley, Ian A (New Journal of Physics)

Direct generation of genuine single-longitudinal-mode narrowband photon pairs - Luo, Kai Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine (New Journal of Physics)

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Formation and interaction of resonance chains in the open three-disk system - Weich, T; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)